2019
DOI: 10.1126/scitranslmed.aav4772
|View full text |Cite
|
Sign up to set email alerts
|

A multimodality test to guide the management of patients with a pancreatic cyst

Abstract: Pancreatic cysts are common and often pose a management dilemma, because some cysts are precancerous, whereas others have little risk of developing into invasive cancers. We used supervised machine learning techniques to develop a comprehensive test, CompCyst, to guide the management of patients with pancreatic cysts. The test is based on selected clinical features, imaging characteristics, and cyst fluid genetic and biochemical markers. Using data from 436 patients with pancreatic cysts, we trained CompCyst t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 37 publications
2
128
0
1
Order By: Relevance
“…MCLs can have mutations in KRAS, while GNAS mutations are highly specific. Overall, almost two thirds of IPMNs and MCNs harbor a mutation in KRAS or GNAS in the cyst fluid 41 . A novel recently-described approach is to combine the most specific clinical features with molecular markers.…”
Section: Cystic Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…MCLs can have mutations in KRAS, while GNAS mutations are highly specific. Overall, almost two thirds of IPMNs and MCNs harbor a mutation in KRAS or GNAS in the cyst fluid 41 . A novel recently-described approach is to combine the most specific clinical features with molecular markers.…”
Section: Cystic Lesionsmentioning
confidence: 99%
“…A novel recently-described approach is to combine the most specific clinical features with molecular markers. A recent study of 862 individuals undergoing surgery for pancreatic cysts, found that a combined molecular and clinical marker panel was more accurate than current clinical features alone, and use of these markers would have decreased the number of unnecessary operations by 60% 41 .…”
Section: Cystic Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Last years, there has been an increasing interest in artificial intelligence (AI)based diagnosis of IPMN and PCN in general. Two study groups have developed AIbased diagnostic algorithms using clinical, imaging, and cyst fluid features to assess the presence of advanced neoplasia with promising results for future implementation in clinical practice [130,131].…”
Section: Surveillancementioning
confidence: 99%
“…[5][6][7][8][9] Beyond endoscopy, computer vision is also being applied quite extensively in abdominal radiology, for instance, to classify and risk stratify pancreatic cysts identified on CT and magnetic resonance imaging, in some cases with algorithms that can integrate other clinical and laboratory data as well. 10,11 To focus only on computer vision, however, creates a too-narrow view of the potential for AI in gastroenterology. There is also enthusiasm and some early progress for AI technologies seeking to reduce the tremendous burden of documentation in electronic health records (EHRs), to automate repetitive tasks, to reduce administrative burdens, and to facilitate quality reporting and analytics.…”
mentioning
confidence: 99%